Improving Speaking Skill for Pursuing Better Education: Getting Used to Speaking English for Students Through Online Learning Courses (Conference on English Language Teaching, 2024)
Speaking skill is one of the most important elements in social interaction especially in preparing better education. This can be done through online courses. This article explores the importance of improving academic speaking skill in pursuing better education through online English courses to support sustainability after graduating from high school. The study used a qualitative case study method. The data were collected from several interviews with four college students who had studied an online English course. The findings revealed that many online English courses facilitate students in improving English speaking skills especially in entering higher education. In addition, the English course provides flexibility and efficiency for the students during joining English course. The implication is discussed in this study.